An Exploration of Locus of Control Levels among Young Adults in Ugandan Universities - Winfred Biribonwa Kyosaba; David Kani Olema; Aloysius Rukundo (East African Journal of Education Studies, 2025)
This study examines locus of control (LOC) orientations among Ugandan university students, investigating how control beliefs influence their behavioural patterns. Employing a concurrent mixed-methods design, we surveyed 527 students (250 males, 277 females) across four institutions and conducted focus group discussions with peer educators and student leaders. The results demonstrated a predominant external LOC orientation (78.2%), with only 21.0% exhibiting combined external-internal LOC. Significant variations emerged across demographic factors: female students and hostel residents showed stronger external LOC tendencies compared to their male and privately accommodated counterparts. Religious affiliation also influenced LOC patterns, though to a lesser degree. These findings substantiate key propositions of the Theory of Planned Behaviour, particularly regarding the relationship between external LOC and increased vulnerability to risky behaviours stemming from diminished perceptions of personal agency. The study reveals how socioeconomic constraints and institutional environments in Uganda's higher education system shape students' control beliefs. Notably, the near-absence of purely internal LOC contrasts with Western studies, suggesting cultural and contextual influences on control orientations. Based on these insights, we propose targeted interventions including university-based empowerment programs, peer mentorship initiatives, and life skills training to cultivate internal LOC attributes. Such measures could enhance students' self-efficacy and promote more adaptive decision-making. The findings contribute to both theoretical understanding of LOC in collectivist educational contexts and practical approaches to student development in resource-constrained settings.
Keywords: Locus of control; Young Adults; Ugandan Universities; Risk Behaviours; Self-efficacy